Environmental Assessment of Al-Hammar Marsh Sediments, Southern Iraq - F. Abdullah, Hind; S. AL-Tawash, Balsam (Iraqi Journal of Science, 2023)
Concentrations and distribution of major, minor, and trace elements werestudied in thirteen sediment samples from Al-Hammar Marsh.Multivariate statistical techniques such as Principal Component Analysis (PCA)and Agglomerative Hierarchal Cluster Analysis (AHCA) as well as pollutionanalysis such as Enrichment Factor (EF) were used to process the data and identifythe possible sources of elemental constituents in sediment samples.Results ofchemical analysis revealed that Major element mean concentrations were in theorder of Ca> Si> K> Mg> and minor elements were in the order of Al> Fe>S>Cl>Ti> P>Mn> Sr> N and trace elements were in the order of Cr> Ni> Zr>V>Zn>Cu>Br> Co>Pb >Mo>As>U> Se> Cd.Mainly increasing of Salinity in Marsh water and sediments led to increasing of Mg, S, Ca, Br, Cl concentrations in Al-Hammar Marsh Sediments.Multivariate statistical techniques PCA and AHCA revealed that V, Zn, As, Se,Mo, Pb, Co, Fe, Ni, and Cu were most probably derived from fertilizers andpetroleum extraction wastes in and near the study site. U (at StR1R) and Sr came fromfertilizers and for U might be from military weapon. Br, Cd, Cl, Ca, S, P and Nindicated anthropogenic source (fertilizers, animal waste, and domestic sewage).While Mg, Cr, Mn were mainly associated with anthropogenic activities (fertilizersand animal wastes). On the other hand Al, Si, Ti, K، and Zr were primarily ofnatural sourcing from erosion of parent rocks. Enrichment Factor gave compatibleresults with PCA and AHCA findings and revealed that Al-Hammar Marshsediments were highly contaminated by S, Mg, Cl, Ca, P, Br, Se, Mo, Ni, Co, Cu,and Sr. and it were minimally contaminated by Zn, V, U, Cr (excluding SR3R), As, Fe,Mn, and N.